Comparison of intranasal and nebulized dexmedetomidine for premedication in pediatric patients: A non-inferiority randomized controlled trial - Shilpi Verma; Pradeep Kumar Bhatia; Vandana Sharma; Sadik Mohammed; Anita Saran (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Dexmedetomidine is a highly selective α-2 adrenoreceptor agonist and has been found to be an effective premedication agent when administered via the intranasal route. We aimed to compare the efficacy of dexmedetomidine premedication administered via intranasal route and through nebulization in pediatric patients. Material and Methods: This non-inferiority randomized controlled trial was conducted after getting approval from institutes ethics committee and informed written parental consent. Sixty-four children aged 2-8 years scheduled for elective surgery under general anesthesia were enrolled and were divided into two groups. Group I (Intranasal, n = 33) received 2 mcg/kg dexmedetomidine via intranasal route and group N (Nebulized, n = 31) received 2 mcg/kg dexmedetomidine through nebulization. The primary outcome was number of patients with satisfactory sedation 30 minutes after premedication at separation from parent. The secondary outcome included ease of medication acceptance, anxiety at parental separation, acceptance of anesthesia mask, perioperative hemodynamics, emergence agitation during recovery and adverse effects. Data collected was analyzed using Chi-square test, Student "t" test and Mann-Whitney U test with the help of SPSS 22. A one tailed P value < 0.025 was considered significant. Results: Demographic profile was comparable between groups. On arrival in OR 27 (81.8%) patients in group I and 21 (67.7%) patients in group N had satisfactory sedation score (P = 0.19). The median (IQR) sedation score was comparable between group I and group N (P = 0.057). Patients in Group I showed significantly better medication and mask acceptance scores (P < 0.0001, P = 0.001 respectively), parental separation anxiety score (P < 0.0001) and emergence agitation score (P = 0.001). There were no significant differences in hemodynamic parameters and adverse effects between the groups. Conclusion: Although nebulized dexmedetomidine is non-inferior to intranasal dexmedetomidine in providing desired level of sedation but intranasal administration had better acceptance of medication and anesthesia mask with lesser anxiety at parental separation and postoperative emergence agitation.